Exploring how absence of judicial freedom undermines press freedom in Ethiopia - Darge, Hailegiorgis Mamo; Woldearegay, Amanuel Gebru (Frontiers in Communication, 2023)
This qualitative phenomenological study explores how private press journalists perceive, narrate and interpret their personal challenges and hardships they faced with the judicial system of Ethiopia. In addition, this study explored lived experiences of the journalists and their effort to fight to get a proper court trial in the country. To explore those challenges, and hardships the study considered a time framework embedded the late Prime Minister of Ethiopia Meles Zenawi's tenure. The study used a theory of Alfred Schutz's "Life World" as a lens to provide a "pure" description of the participants' lived experiences. The theory entails a thorough assessment of the participants' encounters and a focus on their lived experiences concerning lack of freedom of judicial system. The data was obtained through a semi-structured interview, which is widely regarded as the most effective method for gathering information for an Interpretative Phenomenological Analysis study. Interviews with the journalists were conducted and transcribed with the goal of allowing participants to tell their own stories. The interview transcripts were studied one by one, and each transcript was read and reread to uncover themes that were then organized and further investigated. This study discovered that private press journalists undergo a variety of problems, hardships, and sufferings as a result of lack of free judicial system in Ethiopia during Meles Zenawi's nearly quarter-century rule. Thus, we propose that if we want to see true freedom in every dimension, including press freedom, the legal system must be totally free from the grip of political power and cease functioning like a puppet and doing what it is instructed.